2018
DOI: 10.1167/tvst.7.5.27
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Photobonding to Enable Accommodating Intraocular Lens Function

Abstract: PurposeAccommodating intraocular lenses (A-IOLs) require capturing the ciliary muscle forces. Prior work demonstrated strong photo-initiated bonding between strips of capsular bag and poly(2-hydroxyethyl methacrylate); (pHEMA) polymer in an extraocular setting. We demonstrate that photobonding can be achieved intraocularly.MethodsPhacoemulsification was performed in porcine eyes (<24 hours postmortem). A commercial intraocular lens (IOL; pHEMA-MMA material) was inserted in the capsular bag. Surface contact bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…PTB is commonly mediated through green light and photoactive dyes such as rose bengal, which when photoactivated, facilitate amino acid crosslinking reactions mainly through the production of singlet oxygen . This repair method has shown to be valuable in a variety of surgical procedures involving the skin, eye, blood vessels, and vocal cords . However, using the dye alone with green light often does not provide enough mechanical strength in some procedures without extra support from grafts or sutures. , This disadvantage is also shared with many of the commercially available tissue adhesives, which have poor mechanical properties under high tensile loads .…”
Section: Introductionmentioning
confidence: 99%
“…PTB is commonly mediated through green light and photoactive dyes such as rose bengal, which when photoactivated, facilitate amino acid crosslinking reactions mainly through the production of singlet oxygen . This repair method has shown to be valuable in a variety of surgical procedures involving the skin, eye, blood vessels, and vocal cords . However, using the dye alone with green light often does not provide enough mechanical strength in some procedures without extra support from grafts or sutures. , This disadvantage is also shared with many of the commercially available tissue adhesives, which have poor mechanical properties under high tensile loads .…”
Section: Introductionmentioning
confidence: 99%
“…Rose Bengal photobonding (RBPh) had been shown to be effective for sealing corneal incisions [22] and for bonding amnion to the cornea [23]. We have shown that it is possible to use this photo-activated technique to bond polymers such as those typically used for contact lens and IOL manufacturing to capsular tissue [24] as well as full intraocular lenses following phaco-emulsification in a porcine eye model [25].…”
Section: Introductionmentioning
confidence: 99%
“…Using the same photosensitizer and green light source, a hydrophilic polymer sample stained with Rose Bengal and in contact with capsular bag tissue can be quickly (5-10 min) bonded to the capsular bag, with recorded maximum forces higher than those found in the accommodative apparatus. The efficacy and viability of this method to bond hydrophilic polymer strips and entire commercially available IOLs to the capsular bag has been demonstrated, both ex vivo (Marcos et al, 2015) and intraocularly, in a porcine eye model, following cataract surgery procedures (Alejandre-Alba et al, 2018).…”
Section: Introductionmentioning
confidence: 99%